Direct-write 3D printing of NdFeB bonded magnets. Issue 1 (2nd January 2018) - Compton, Brett Gibson; Kemp, James William; Novikov, Timofei V.; Pack, Robert Cody; Nlebedim, Cajetan I.; Duty, Chad Edward; Rios, Orlando; Paranthaman, M. Parans
ABSTRACT: We report a method to fabricate Nd–Fe–B (NdFeB) bonded magnets of complex shape via extrusion-based additive manufacturing (AM), also known as 3D-printing. We have successfully formulated a 3D-printable epoxy-based ink for direct-write AM with anisotropic MQA NdFeB magnet particles that can be deposited at room temperature. The new feedstocks contain up to 40 vol.% MQA anisotropic NdFeB magnet particles, and they are shown to remain uniformly dispersed in the thermoset matrix throughout the deposition process. Ring, bar, and horseshoe-type 3D magnet structures were printed and cured in air at 100°C without degrading the magnetic properties. This study provides a new pathway for fabricating NdFeB bonded magnets with complex geometry at low temperature, and presents new opportunities for fabricating multifunctional hybrid structures and devices.